Testimonial - Beg, Wazir; Chalmers' Church Dialectic Association (1869)
Presented by the members of Chalmers' Church Dialectic Association in token of appreciation.
Manuscript reference: NLA MS 3435.
Sir John Ferguson Collection.
Keywords: Beg, Wazir; Clergy